REE DISTRIBUTION IN THE LI-BEARING METASOMATIZED METAPELITES OF THE ETYKA ORE FIELD, EASTERN TRANSBAIKALIA - Kuznetsova L.G.; Zagorskii V.E. (My University, 2001)
The unique Li-bearing metasomatic deposit formed in the outer contact of the Etyka Ta-bearing amazonite granite massif was studied. The metasomatites were formed in the pregranite and syngrahite stages. The pregranite stage was characterized by temperature variations and related fluctuations in the fluid and alkalinity regimes. Unlike the syngranite greisenization, the pregranite high-temperature greisenization was associated with REE introduction progressively enhancing with an increase in fluid (F, P) activity. The REE precipitation in different zones of the metasomatic columns was not uniform and was controlled by REE affinity to volatiles, as well as by the alkalinity regime and presence of favorable geochemical barriers and REE-concentrating minerals such as fluorides (fluorite, weberite, sellaite) and phosphates (Sr-bearing apatite, goyazite-gorceixite, and monazite).